Dynamically vulcanized EPDM (ethylene-propylenediene polymer)/ PP(polypropylene) polymer blend: Performance index (PI) - (:unkn) unknown (My University, 2010)
A Performance Index measure is presented to elucidate the overall property behavior of dynamically vulcanized high rubber content ethylene-propylene-diene (EPDM), polypropylene (PP) anddicumyl peroxide as curing agent. After melt mixing the polymers with a twin screw extruder, specimens for tensile, hardness test measurements are obtained by injection molding. Strength at break, elongation, permanent deformation, hardness (Shore D), melt flow index (MFI), crosslink density, thermal transition temperatures and fracture surfaces of the polymer blends are determined experimentally from injection-molded test samples. © MD Publications Pvt. Ltd.
Keywords: Dicumylperoxide; Dynamic vulcanization; Overall performance; Performance index; Polymer blends; Polypropylene